Studi Identifikasi Kelembagaan Sosial Masyarakat Nelayan Di Desa Muara Pasir Kecamatan Tanah Grogot Kabupaten Paser - Nandang Triyana; Fitriyana; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
A Study on the Identification of Social Institutions for the Fishermen Community in Muara Pasir Village, Tanah Grogot District, Paser Regency. Faculty of Fisheries and Marine Sciences, Mulawarman University. (Supervised by Hj. Fitriyana and Oon Darmansyah). This study aims to identify the social institutions that exist in the fishing community in Muara Pasir village, both formal and informal social institutions. This research was conducted for 19 months starting from October 2019 to January 2021. The sample method used was purposive sampling with a sample of 49 respondents. The analytical method used is descriptive qualitative analysis in the form of a narrative. The results of this study indicate that the social institutions in Muara Pasir Village consist of formal institutions, namely the Fishermen Partners Institute, the Sinar Pasifik fishing group, and the Leger fishermen group. Furthermore, the informal social institutions found in the fishing community in Muara Pasir Village are Community Service or mutual assistance. Keywords: Social Institution, Institutional Type, Formal and Informal.